Shelf-life extension and postharvest quality improvement of tomato (Solanum lycopersicum L.) using pre- and postharvest treatments - Mazumder, Mohammad Nurun Nabi (2022)
Tomato (Solanum lycopersicum L.) is a popularly consumed and mostly cultivated vegetable fruit all over the world. For the fresh market, tomatoes are typically hand-harvested due to their delicate skins and their need to be picked at optimal ripeness. Tomatoes are highly perishable and poor postharvest handling contributes to huge losses of as high as 20%. Therefore, this study was conducted to determine the effects of pre-and postharvest calcium chloride (CaCl2) treatments along with gamma irradiation on the growth, yield, quality, and shelf life of lowland tomato varieties in Malaysia. In the first experiment, four tomato varieties known as MT-1, MT-3, 303, and 105 were selected and applied with foliar CaCl2 (0.0, 1.0, 1.5, and 2.0%, w/v) in the morning after one week of fruit initiation for agronomical traits. Application of 2% CaCl2 was demonstrated as the most effective to control the physiological disorder like blossom end rot of 303 and 105 varieties. The CaCl2 minimized the weight loss (30%) and declined the disease incidence and disease severity by maintaining the firmness of MT-3 tomato fruits. After harvesting, all the fruits were kept at ambient conditions (28 ± 2℃ and 75 ± 5% RH) for 20 days. Among all the varieties, MT-3 along with 2% CaCl2 performed better in maintaining the postharvest quality and was able to extend the shelf-life up to 2- 4 days by increasing the fruit firmness, declining the rate of respiration and ethylene production. The different maturity stages of tomato respond differently to CaCl2, the second experiment was conducted to investigate the effects of different maturity stages and postharvest dipping with 0.0, 1.0, 1.5, and 2.0% of CaCl2 (w/v) for 10 minutes on postharvest performance, antioxidant and plant defence enzyme activity stored at ambient conditions (28 ± 2℃ and 75 ± 5% RH). Fruits of mature green stage treated with 2% CaCl2 significantly declined ethylene production (15.53%) and delayed colour development by declining the lycopene content (45%) as well as accelerating the defence enzyme activities as compared to control. The final experiment was involved with mature green stage of MT3 tomatoes that had been inoculated with Fusarium solani and then exposed to gamma radiations (0.0, 1.0, 2.0, and 3.0 kGy) in order to extend shelf life. The fruits were then stored at ambient conditions (28 ± 2℃ and 75 ± 5% RH) for 15 days. The higher doses of 3 kGy resulted in a significant reduction of ethylene (41.23%), respiration (38.77%), non-marketable fruits (71.23%), and physiological weight loss (28.47%) than the control and lower doses samples. Additionally, the gamma radiations in the highest doses (3.0 kGy), prolong the shelf-life by up to 2- 4 days than the control and lower doses samples. In storage conditions, the tomato fruits increase the defence enzymes activity of POD (25.67%), PPO (17.33%), and PAL (21.58%) at 3.0 kGy relative to that of control samples. In conclusion, the application of pre-and postharvest CaCl2 on MT-3 (harvested at mature green) could effectively extend the postharvest shelf life for up to 4 days when held at ambient temperature. Besides that, gamma radiation at 3.0 kGy can be successfully used to minimize the losses due to fungal infection, especially Fusarium solani, which leads to the extension of the shelf-life of tomato fruits.